Public Investment as an Engine of Growth - Warner, Andrew (IMF Working Papers; Working Paper, 2014)
This paper looks at the empirical record whether big infrastructure and public capital drives have succeeded in accelerating economic growth in low-income countries. It looks at big long-lasting drives in public capital spending, as these were arguably clear and exogenous policy decisions. On average the evidence shows only a weak positive association between investment spending and growth and only in the same year, as lagged impacts are not significant. Furthermore, there is little evidence of long term positive impacts. Some individual countries may be exceptions to this general result, as for example Ethiopia in recent years, as high public investment has coincided with high GDP growth, but it is probably too early to draw definitive conclusions. The fact that the positive association is largely instantaneous argues for the importance of either reverse causality, as capital spending tends to be cut in slumps and increased in booms, or Keynesian demand effects, as spending boosts output in the short run. It argues against the importance of long term productivity effects, as these are triggered by the completed investments (which take several years) and not by the mere spending on the investments. In fact a slump in growth rather than a boom has followed many public capital drives of the past. Case studies indicate that public investment drives tend eventually to be financed by borrowing and have been plagued by poor analytics at the time investment projects were chosen, incentive problems and interest-group-infested investment choices. These observations suggest that the current public investment drives will be more likely to succeed if governments do not behave as in the past, and instead take analytical issues seriously and safeguard their decision process against interests that distort public investment decisions.